Drip fertigation with straw incorporation significantly reduces N2O emission and N leaching while maintaining high vegetable yields in solar greenhouse production. (15th March 2021) - Zhao, Yiming; Lv, Haofeng; Qasim, Waqas; Wan, Li; Wang, Yafang; Lian, Xiaojuan; Liu, Yanni; Hu, Jing; Wang, Zhengxiang; Li, Guoyuan; Wang, Jingguo; Lin, Shan; et al.
Abstract: Approximately 1/3 of vegetables in China are produced in solar greenhouses. Most farmers use conventional irrigation with over fertilisation (CIF), thereby applying approximately 2000 kg N ha −1 fertiliser over two cropping seasons per year. Here, we tested the effect of drip irrigation with reduced fertilisation (DIF) combined with straw incorporation on reducing N2 O emissions and nitrogen leaching from solar greenhouse vegetable production systems. Over three consecutive tomato cropping seasons, N2 O emissions and nitrogen leaching were monitored in high temporal resolution, thereby producing a unique dataset. Compared to CIF, the realised drip fertigation scheme reduces N2 O emission and nitrogen leaching of nitrate and dissolved organic nitrogen by approximately a factor of 5–10 (N2 O-DIF: 10.3, CIF: 47.5 kg N ha −1 yr −1 ; N leaching-DIF: 83.6, CIF: 863 kg N ha −1 yr −1 ). Straw incorporation in CIF, though advantageous for soil health, resulted in pollution swapping as soil N2 O emissions increased while NO3 − leaching losses decreased. On the contrary, no significant negative environmental N effects of straw incorporation were found for DIF. As crop productivity was not affected by straw incorporation, neither for CIF nor for DIF, our study provides a sound basis for policy advice to recommend farmers to adopt drip fertigation combined with straw application. Wide scale adoption of this technique will result in reductions of environment N losses, alleviate major soil degradation signs, including soil acidity, nutrient imbalance and deterioration of soil microbial community structure, while allowing to maintaining high yields of vegetables in solar greenhouse production systems. Graphical abstract: Image 1 Highlights: Drip fertigation significantly reduced N2 O emission by 80% and N leaching by 90%. Most N2 O emission and N leaching occurred in the first 20-day after basal fertigation. Total environment N losses was higher in autumn-winter than in winter-spring season. Straw addition increased N2 O emissions and decreased N leaching in flood fertigation. Straw addition had no effects on environmental N loss in drip fertigation. Abstract : Drip fertigation combined with straw incorporation significantly reduces N2 O emission and N leaching, improves soil health, while sustaining high yields.